2015
DOI: 10.1007/s11357-015-9793-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the individual responsiveness to resistance training periodization

Abstract: This study was designed to compare the effects of linear periodization (LP) and undulating periodization (UP) on functional capacity, neuromuscular function, body composition, and cytokines in elderly sedentary women. We also aimed to identify the presence of high responders (HR), medium responders (MR), and low responders (LR) for irisin, interleukin-1 beta (IL-1β), toll-like receptor-4 (TLR-4), and brainderived neurotrophic factor (BDNF) to resistance training (RT). Forty-nine elderly women were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 33 publications
3
45
0
5
Order By: Relevance
“…Our results showed that after 8 weeks of resistance training, irisin levels and mRNA expression of UCP1 in subcutaneous white adipose tissue and muscle FNDC5 increased. Similarly, Prestes et al (2015) (31) showed that high-intensity resistance training increased irisin levels after 16 weeks of training in sedentary elderly women. Increases in serum irisin, FNDC5 , or PGC1-α after chronic exercise have been reported in mice and humans (1, 17).…”
Section: Discussionmentioning
confidence: 89%
“…Our results showed that after 8 weeks of resistance training, irisin levels and mRNA expression of UCP1 in subcutaneous white adipose tissue and muscle FNDC5 increased. Similarly, Prestes et al (2015) (31) showed that high-intensity resistance training increased irisin levels after 16 weeks of training in sedentary elderly women. Increases in serum irisin, FNDC5 , or PGC1-α after chronic exercise have been reported in mice and humans (1, 17).…”
Section: Discussionmentioning
confidence: 89%
“…This strategy has yielded valuable insight into potential cellular and molecular regulators of human RT-induced myofiber hypertrophy (Bamman et al 2007; Kim et al 2007; Petrella et al 2008; Mayhew et al 2011; Thalacker-Mercer et al 2013). We have since validated the utility of the model (Stec et al 2016) and today similar strategies used by a number of research teams continue to bear fruit (Davidsen et al 2011; Prestes et al 2015; Ahtiainen et al 2016; Ogasawara et al 2016). Of course all participants in RT trials benefit to varying degrees in other ways (Bamman et al 2007; Bickel et al 2011; Churchward-Venne et al 2015) (e.g., strength gains, functional mobility improvements, etc.)…”
Section: Leveraging Human Interindividual Response Heterogeneitymentioning
confidence: 93%
“…Nine studies 23, 34, 39, 41, 51, 54, 59, 65, 74 showed that chronic exercise increased circulating Irisin, while 12 studies 12, 16, 18, 22, 33, 37, 42, 45, 53, 57, 62, 70 showed no effects of chronic exercise on circulating Irisin, and two studies showed that chronic exercise decreased circulating Irisin 55, 56 , in both healthy and clinical populations.…”
Section: Resultsmentioning
confidence: 97%